Evaluation of Zahedan Resilience against Water and Drought Crisis - fatemeh yadegarifar; mohammadreza poodineh; morteza esmaelnejad (تحقیقات کاربردی علوم جغرافیایی)
In the meantime it can cause serious and irreparable damage to other social, economic and structural sectors of society. A look at the history of human life on Earth shows that human beings have always been exposed to all kinds of natural hazards. Natural hazards have many types, one of which is drought and water crisis. The recent droughts in Iran and the severity of the damage indicate the continued vulnerability of urban and rural areas. At present, drought management in our country is based on crisis management and thus less attention is paid to drought impacts and preparedness. Therefore, the purpose of this study is to evaluate the resilience of Zahedan city against water crisis and drought. The present study is applied in terms of purpose and in terms of research, descriptive and analytical. The statistical population of the study is all households in Zahedan city based on the census of 1395 168480 households (672589 people). From the household heads, a sample size of 383 people was selected randomly using Cochran formula. Descriptive statistics and inferential statistics were used to analyze the findings. The results of one-sample t-test show that the economic, social and institutional resiliency status in Zahedan city is lower than the average (2.815, 2.873 and 2.886, respectively); The results showed that Zahedan city is not in a good position in terms of resilience to drought and water crisis and this city has many water problems in rural areas and Zahedan city. Rural water shortages and droughts have caused extensive damage to farmers and ranchers. The effects of the water crisis on the economic, social and environmental structure of the villages have been very negative and these negative effects have ultimately led to the migration of villagers to Zahedan